Critical Thoughts on American Social Work and the Crisis of Modernity: Lessons From Theory and Current Events. Issue 1 (2nd January 2018) - Cherry, Kevin
ABSTRACT: Social work in America is at a curious junction: continue down the status quo path of professionalization or embrace an antagonistic and critical, political stance toward global institutions and the logics of injustice. This article defines the junction as a crisis of modernity wherein the institutions and logics reflecting modernity's primary forms—capitalism and democracy—suffer material and affective setbacks. The New Social Work Left movement is advocated as a useful response to the crisis of modernity, and initial strategies are offered for fostering a New Social Work Left in the United States.